Genus-Wide Pan-Genome Analysis of Populus bZIP Transcription Factors with Reanalysis of Public Salt-Stress Transcriptomes - Qi Lin; Yayu Guo; Houling Wang (Plants, 2026)
Basic leucine zipper (bZIP) transcription factors regulate plant development and stress responses, but their genus-wide diversity in Populus remains unclear. We analyzed 19 Populus genomes and retained 1764 bZIP proteins, including 21 independent new loci and four annotation corrections. Of these, 1762 were assigned to 79 orthologous gene groups (OGGs), comprising 43 core, 20 soft-core, 15 shell and one cloud OGG, of which 59 showed copy-number variation. Phylogenetic analysis assigned 74 representative pangenes to 13 subfamilies, with five remaining unclassified and motif patterns differing among subfamilies. Whole-genome duplication (WGD)/segmental duplication accounted for 81.0% of OGG-assigned proteins and contributed predominantly to the conserved component. Although 72.2% of bZIP proteins overlapped a transposable element within the gene body or 2-kb flanks, this proportion was modestly lower than in matched non-bZIP genes, and copy-number-variable OGGs showed no greater TE coverage than invariant OGGs. Among retained homologous comparisons, 97.6% had Ka/Ks ≤ 1, supporting predominant purifying selection. Across the heterogeneous public salt-stress RNA-seq datasets analyzed, no OGG showed a significant, directionally concordant response in at least two Populus taxa. These results reveal a conserved bZIP framework shaped mainly by ancient duplication alongside variable genomic contexts and transcriptional responses.